Person to person [videorecording (DVD)] - Jacobson, Abbi; Cera, Michael; Gevinson, Tavi, 1996- (Magnolia Home Entertainment, 2017)
During a single day in New York City, a variety of characters grapples with the mundane, the unexpected, and the larger questions permeating their lives. An investigative reporter struggles with her first day on the job, despite help from her misguided boss; a rebellious teen attempts to balance her feminist ideals with other desires; and a young man seeks to reconcile with his ex-girlfriend, even as her brother threatens revenge.